Global Climate Change as Perceived by Elementary School Teachers in Yogyakarta , Indigenous Psychology Approach - Aquilina Tanti Arini; Ratna Juwita Ghazali; Arti Satiti; Mintarsih Mintarsih; Kwartarini W Yuniarti (Faculty of Psychology, Universitas Gadjah Mada, 2017)
This study aimed to describe how global climate change was perceived by teachers of elementary schools. The subjects were 111 teachers from 7 elementary schools in Yogyakarta City and Sleman district. The data were collected using open-ended questions (including perception about the weather, feeling evoked by global warming words and free responses related to global warming issues). The data were analyzed using the technique of qualitative and quantitative content analysis with Indigenous Psychology Approach. The result showed that only one teacher reported that there was no weather anomaly, while 110 teachers reported that they perceived weather anomaly. Of those who perceived weather anomaly mostly referred to natural conditions (including global climatic condition and environmental destruction) and human behavior as its causes. Responses about feeling as evoked by global warming word were classified into three categories, i.e. emotional, physical and irrelevant responses. Free responses about global warming were classified into four categories respectively from the highest frequency of responses: prevention (including the statement “must be prevented”, prevention behaviors and prevention efforts), states (including the weather states and feeling), causes (including technological advances and human behavior generally), and others. The research finding was discussed in the frame of environmental concern as a means of character education in elementary school.